Integrated genomic and transcriptomic analysis improves disease classification and risk stratification of MDS with ring sideroblasts - Todisco, Gabriele; Hellström-Lindberg, Eva (Karolinska Institutet, 2023)
Full transcriptome (RNA-sequencing) from bulk CD34+ bone marrow mononuclear cells from MDS patients with ring sideroblasts. CD34+ cells were isolated from the MNC using AUTO-MACS with double-separation option (Miltenyi Biotec, Germany) and submitted for RNA extraction. RNA was extracted with RNeasy Microkit (Qiagen, Hilden, Germany) and treated with DNase, according to manufacturer instruction. RNA integrity number was estimated using Agilent RNA 6000 Pico (Agilent Technologies, Palo Alto, CA) and was greater than 6.5 for all the samples (median 8.2). The RNA-sequencing (RNA-seq) libraries were prepared from total RNA using SMARTer Stranded Total RNA-Seq Kit v2 Pico Input Mammalian with enzymatic ribosomal depletion (Takara Bio, Japan). Libraries were sequenced using the Novaseq 6000 with paired-end 150bp configuration. The molecular data were integrated with clinical information aiming to improve prognosis prediction in this hematologic malignancy.

The dataset consists of 2 files:
- FASTQ_RS.tar.gz: compressed folder that includes 258 fastq files
- metadata_RS.xlsx

The total size of the dataset is approximately 1 TB.

Heltranskriptom-sekvensering (RNA-seq) från CD34-uttryckande mononukleära benmärgsceller från patienter med myelodysplastisk syndrom med ringsideroblaster (MDS-RS). CD34-uttryckande celler isolerades från mononukleära benmärgsceller via instrumentet AUTO-MACS med dubbelseparation (Miltenyi Biotec, Germany). RNA extraherades från CD34-uttryckande celler via RNeasy Microkit (Qiagen, Hilden, Germany) och behandlades därefter med DNase i enlighet med tillverkarens instruktion. RNA integritetsnumret uppskattades sedan via Agilent RNA 6000 Pico (Agilent Technologies, Palo Alto, CA) och var högre än 6.5 i alla prover (median 8.2). RNA sekvenseringsbiblioteken sattes upp från allt RNA via SMARTer Stranded Total RNA-Seq Kit v2 Pico Input Mammalian med enzymatisk degradering av ribosomalt RNA (Takara Bio, Japan). RNA-biblioteken sekvenserades sedan på Novaseq 6000 med ”paired-end 150bp” inställning. Slutligen kombinerade vi molekylära och kliniska data i syfte att hitta nya prognostiska markörer och förbättra karaktärisering av sjukdomen hos patienter med MDS.

Datasetet består av två filer:
- FASTQ_RS.tar.gz: komprimerad mapp innehållande 258 fastq-filer
- metadata_RS.xlsx

Datasetets totala storlek är ca 1 TB.
Integrated genomic and transcriptomic analysis improves disease classification and risk stratification of MDS with ring sideroblasts
Keywords: Hematologic Diseases; Blodsjukdomar; Myelodysplastic Syndromes; Myelodysplastiskt syndrom; Myelodysplastic-Myeloproliferative Diseases; Myelodysplastiska-myeloproliferativa syndrom; Human health and safety; Människors hälsa och säkerhet; cancer; neoplasms; tumors; Medical Genetics and Genomics; Medicinsk genetik och genomik; Hematology; Hematologi; Cancer and Oncology; Cancer och onkologi; Basic Cancer Research; Basal cancerforskning